Implementing the WIPO development agenda country specific recommendation: a comprehensive approach - Aluko, Olajumoke. A (2015)
This research looks into the implementation of the WIPO Development Agenda recommendation that intellectual property technical assistance (IPTA) programs to developing countries should be country-specific in their design, process of evaluation and delivery. Using the example of Malaysia and Kenya, this thesis identifies and examines local factors in Malaysia and Kenya to determine what makes them specific to these countries and how significant they are to the effectiveness of IPTA programs. Developing countries’ struggle in adapting their national systems to meet the global IP standards resulted in the provision of IPTA programs that have been criticized as ineffective due to the former one size fits all approach that did not tailor the programs to each developing country’s needs. The WIPO Development Agenda recommended a country-specific approach to address the previous approach. Although this recommendation has the potential to significantly revise the way WIPO provides technical assistance (TA) to developing countries, this research states that without proper implementation there is the possibility that WIPO IPTA programs will fall back into its old ways. This research tests the country-specific recommendation in Malaysia and Kenya by using a historical approach into understanding why these countries have local factors that permeate almost every aspect of their development, what makes these factors country-specific and how these factors could impact IPTA programs. The research finds that even though the local conditions in Malaysia and Kenya appear similar, the historical perspective show how the local conditions evolved into factors specific to each country with varying degrees of impact on IPTA programs. The findings suggest that implementing this recommendation would need to go beyond identifying the relevant local conditions, it requires an understanding of what makes them country-specific to help determine how to factor them into the design and delivery of IPTA programs.